Revision strategy for malunited tibial plateau fracture caused by failure of initial treatment - Jiang Liangjun; Zheng Qiang; Pan Zhijun; Hang Li (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to evaluate our treatment algorithm and results in revision surgery of malunited tibial plateau fracture after failure of initial treatment. Methods: Our revision strategy was as follows: First, we determined the presence of any infection. Second, we determined whether the patient required total knee arthroplasty (TKA). Third, based on the characteristics of the tibial plateau fracture malunion, patients underwent one of the following surgical methods to achieve reduction: original fracture line osteotomy, tibial tubercle + original fracture line osteotomy, fibula head + original fracture line osteotomy, and metaphyseal open window reduction rod technique. The results was assessed with healing time, Rasmussen score, knee range of motion and complication rates. Results: A total of 25 patients 16 men and 9 women; Mean age: 47.4 years (range: 35–63 years) underwent tibial plateau fracture revision operation. The time interval between the two surgeries was 2–24 months. The follow-up time was 12–30 months, and the operation time was 120–300 min. All patients received bone union at the last follow-up. The healing time was 3–6 months. The postoperative Rasmussen score was 19–29 (mean 23.8) compared with 14.4 points before the operation (p < 0.05). The postoperative knee joint activity was 60–110° (mean 95.0°), compared with 57.8° before the operation (p < 0.05). Six patients still had a 2-mm collapse on the articular surface, and 4 patients still had slight valgus (<5°). Except for 2 TKA cases, fracture reduction was excellent in 15 cases and good in 8 cases, with a good rate of 100%. Superficial wound infections occurred in 3 patients. Conclusion: Because revision of tibial plateau fracture malunion caused by failure of initial treatment is difficult, it is necessary to create a detailed surgical plan before the operation. Satisfactory clinical effects can be obtained if the correct revision strategy is used. The key to success is adopting a proper revision strategy according to the unique characteristics of the patient's tibial plateau fracture malunion. Level of Evidence: Level IV, Therapeutic Study. Keywords: Malunited tibial plateau fracture, Revision strategy, Intra-articular osteotomy, Articular surface reduction, Lower limb alignment